Cortisol and creatinine in amniotic fluid - Maradiegue M., Eduardo (2015)
The determination of creatinine and free cortisol in amniotic fluid conducted in 150 patients of the General Hospital Cayetano Heredia Base, of which 117 were pregnant without labor, laboring 21 and 12 caesarean sections without labor. In pregnant without labor (31- 42 weeks) cortisol determinations varied without statistical significance; creatinine values were significantly elevated between 36-37 weeks. During labor cortisol values increase with statistical significance compared with those obtained in patients cesarean without labor; no difference in creatinine values.